2016
DOI: 10.1186/s12890-016-0325-y
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical course of anti-glycyl tRNA synthetase (anti-EJ) antibody-related interstitial lung disease pathologically proven by surgical lung biopsy

Abstract: BackgroundAnti-glycyl-tRNA synthetase (anti-EJ) antibody is occasionally positive in patients with interstitial lung disease (ILD). We aimed to define the clinical, radiological and pathological features of patients with anti-EJ antibody-positive ILD (EJ-ILD).MethodsWe retrospectively analyzed the medical records of 12 consecutive patients with EJ-ILD who underwent surgical lung biopsy.ResultsThe median follow-up time was 74 months (range, 17–115 months). The median age was 62 years (range, 47–75 years). Seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 34 publications
2
28
0
Order By: Relevance
“…Previous studies have shown that combination therapy improved the findings of PFTs and chest HRCT scans in acute or subacute progressive PM/DM-ILD [22, 25-27]. We previously reported the importance of combination therapy, which should be on the list of options to prevent relapse in anti-EJ ILD [10]. However, it is controversial whether all ARS-ILD patients need corticosteroids in addition to the other immunosuppressive drugs they are taking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that combination therapy improved the findings of PFTs and chest HRCT scans in acute or subacute progressive PM/DM-ILD [22, 25-27]. We previously reported the importance of combination therapy, which should be on the list of options to prevent relapse in anti-EJ ILD [10]. However, it is controversial whether all ARS-ILD patients need corticosteroids in addition to the other immunosuppressive drugs they are taking.…”
Section: Discussionmentioning
confidence: 99%
“…Although some patients with rapidly progressive ARS-ILD have a poor prognosis in the short run, their overall prognosis is relatively good [6, 7]. However, because of frequent recurrence and ARS-ILD refractory to therapy, some patients progress to pulmonary fibrosis over the long run despite initial improvement [8-10]. Some patients are forced to use home oxygen therapy, while a few undergo lung transplantation in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Interstitial lung disease (ILD) is a common complication seen in 20–78% of patients with PM/DM and can be a prognostic determinant [38]. Particularly, patients with DM and clinically amyopathic DM (CADM) frequently develop an acute and severe form of ILD [4, 5].…”
Section: Introductionmentioning
confidence: 99%
“…First, treatment response at 1 year (including at 1 year ± 6 months) based on changes in pulmonary function testing (PFT) results was defined as the %change of the initial value. Patients were assigned to the Improved or Worsened group based on increases or decreases, respectively, of >10% in FVC and >15% %diffusing capacity of lung carbon monoxide (%DL CO ) . Second, if PFT was repeatedly performed at least 12 months after the initial assessment, long‐term change in respiratory function was evaluated.…”
Section: Methodsmentioning
confidence: 99%
“…Other diagnoses in the remaining 30 patients included acute inflammatory findings such as organizing pneumonia and alveolar epithelial injury and interstitial cellular infiltration surrounded by hyaline membrane collapse, which was more prominent in unclassifiable IP than in f-NSIP as we reported previously. 15 We thought these subjects were comparable to a variant of organizing pneumonia with supervening fibrosis or a fibrosing variant of organizing pneumonia. 3,16 Patients with CTD fulfilled each of the standard criteria.…”
Section: Study Samplementioning
confidence: 98%